K⊂{[FeII(Tp)(CN)3]4[CoIII(pzTp)]3[CoII(pzTp)]}: a neutral soluble model complex of photomagnetic Prussian blue analogues12. Issue 8 (6th June 2016) - Garnier, D.; Jiménez, J.-R.; Li, Y.; von Bardeleben, J.; Journaux, Y.; Augenstein, T.; Moos, E. M. B.; Gamer, M. T.; Breher, F.; Lescouëzec, R.
Abstract : We report a new K⊂[Fe4 Co4 ] cyanide box: a true soluble model of the photomagnetic FeCo Prussian blue analogues, which also shows photo-switchable SMM properties and remarkable redox versatility. Abstract : Straightforward access to a new cyanide-bridged Fe4 Co4 "molecular box" containing a potassium ion, namely K⊂{[Fe II (Tp)(CN)3 ]4 [Co III ( pz Tp)]3 [Co II ( pz Tp)]} (1 ) (with Tp and pz Tp = tris- and tetrakis(pyrazolyl)borate, respectively), is provided, alongside its full characterisation. A detailed analysis of the molecular structure (X-ray diffraction, mass spectrometry, NMR spectroscopy) and electronic properties (EPR spectroscopy, SQUID magnetometry, UV/Vis spectroscopy, cyclic voltammetry) reveals that1 shows slow magnetic relaxation and a remarkable photomagnetic effect at low temperature which is reminiscent of some FeCo Prussian Blue Analogues (PBAs), and is ascribed to a photo-induced electron transfer. However, in contrast with these inorganic polymers, the overall neutral compound1 is soluble and remarkably stable in organic solvents such as CH2 Cl2 . Moreover, 1 shows interesting redox versatility, with electrochemical experiments revealing the possible access to six stable redox states.